A survey of factors associated with the successful recognition of agonal breathing and cardiac arrest by 9-1-1 call takers: design and methodology - Kasaboski Ann (BMC Emergency Medicine, 2009)
Abstract Background Cardiac arrest victims most often collapse at home, where only a modest proportion receives life-saving bystander cardiopulmonary resuscitation. As many as 40% of all sudden cardiac arrest victims have agonal or abnormal breathing in the first minutes following cardiac arrest. 9-1-1 call takers may wrongly interpret agonal breathing as a sign of life, and not initiate telephone cardiopulmonary resuscitation instructions. Improving 9-1-1 call takers' ability to recognize agonal breathing as a sign of cardiac arrest could result in improved bystander cardiopulmonary resuscitation and survival rates for out-of-hospital cardiac arrest victims. Methods/Design The overall goal of this study is to design and conduct a survey of 9-1-1 call takers in the province of Ontario to better understand the factors associated with the successful identification of cardiac arrest (including patients with agonal breathing) over the phone, and subsequent administration of cardiopulmonary resuscitation instructions to callers. This study will be conducted in three phases using the Theory of Planned Behaviour. In Phase One, we will conduct semi-structured qualitative interviews with a purposeful selection of 9-1-1 call takers from Ontario, and identify common themes and belief categories. In Phase Two, we will use the qualitative interview results to design and pilot a quantitative survey. In Phase Three, a final version of the quantitative survey will be administered via an electronic medium to all registered call takers in the province of Ontario. We will perform qualitative thematic analysis (Phase One) and regression modelling (Phases Two and Three), to determine direct and indirect relationship of behavioural constructs with intentions to provide cardiopulmonary resuscitation instructions. Discussion The results of this study will provide valuable insight into the factors associated with the successful recognition of agonal breathing and cardiac arrest by 9-1-1 call takers. This will guide future interventional studies, which may include continuing education and protocol changes, in order to help increase the number of callers appropriately receiving cardiopulmonary resuscitation instructions, and save the lives of more cardiac arrest victims. Trial registration Clinicaltrials.gov NCT00848588